2011
DOI: 10.1523/jneurosci.3299-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 Promotes Glioma Cell Invasion and Tumor Progression

Abstract: Gliomas are highly invasive, lethal brain tumors. Tumor-associated proteases play an important role in glioma progression. Annexin A2 is overexpressed in many cancers and correlates with increased plasmin activity on the tumor cell surface, which mediates degradation of extracellular matrix and promotes neoangiogenesis to facilitate tumor growth. In this study, we used two glioma cell lines, mouse GL261-EGFP and rat C6/lacZ, as well as stable clones transfected with an annexin A2 knockdown construct. We find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 80 publications
6
101
0
Order By: Relevance
“…We have identified a number of annexins in our study to be overexpressed in GBM tumors including ANXA1 (log 2 ratio 3.91), ANXA2 (log 2 ratio 2.78), and ANXA5 (log 2 ratio 1.35). Previous studies have shown that ANXA2 and ANXA5 promote glioma cell invasion and tumor progression and are shown to be overexpressed in angiogenic compared with invasive GBM tumors (57,70). ANXA1, the annexin with the greatest magnitude of GBM overexpression in our study, has been found to be a major component in necrotic tumor cell-derived stimulants of the growth of GBM via the activation of formyl peptide receptor (FPR1) (69).…”
Section: Discussionsupporting
confidence: 49%
“…We have identified a number of annexins in our study to be overexpressed in GBM tumors including ANXA1 (log 2 ratio 3.91), ANXA2 (log 2 ratio 2.78), and ANXA5 (log 2 ratio 1.35). Previous studies have shown that ANXA2 and ANXA5 promote glioma cell invasion and tumor progression and are shown to be overexpressed in angiogenic compared with invasive GBM tumors (57,70). ANXA1, the annexin with the greatest magnitude of GBM overexpression in our study, has been found to be a major component in necrotic tumor cell-derived stimulants of the growth of GBM via the activation of formyl peptide receptor (FPR1) (69).…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies have reported that Annexin 1-deficient neutrophils exhibit enhanced transmigration in vivo [35]. Annexin A6 can modulate chick cranial neural crest cell emigration [36] and Annexin A2 can promote glioma cell invasion and tumor progression [37]. The present study showed that deletion of endogenous Annexin A3 reduced the invasion/migration of gastric cancer cells, indicating the positive role of Annexin A3 in gastric cancer cell invasion.…”
Section: Discussionsupporting
confidence: 61%
“…Annexin A2 (ANXA2) is a member of the annexin family (Diaz et al, 2004), and plays important roles to regulate DNA synthesis (Yuan et al, 2007), cell proliferation (Wu et al, 2012), cytoskeleton reorganization (Singh et al, 2004), tumor invasion (Zhai et al, 2011), and metastasis (Zhou et al, 2012). The excessive expression of ANXA2 was reported to enhance the malignancy of numerous cancers in digestion system (Emoto et al, 2001;Esposito et al, 2006;Mohammad et al, 2008;Nedjadi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%